Homiletical aesthetics: A paradigmatic proposal for a holistic experience of preaching. Issue 4 (January 2017) - Yang, Sunggu
The article is a proposal for a paradigmatic change in homiletical pedagogy. In North America today, most homiletical training at the seminary or divinity school is either text-driven or know-how-driven (or, at times, topic-driven). Thus, the homiletical training focuses on (1) how to exposit a text for a key topic, (2) how to structure a sermon, (3) how to deliver a message, and (4) how to analyze the text-driven sermon. While admitting the usefulness of this current textual or know-how pedagogy, the article suggests the addition of a holistic-aesthetic component of preaching, which I will later call numen -participatory education or a numinous pedagogy of preaching. This proposed pedagogical paradigm has two great advantages that the ecclesial situation today demands: (1) the spiritual formation of the preacher and (2) the holistic-aesthetic and multisensory exposition and experience of the text both by the preacher and the audience.